Thiopurines correct the effects of autophagy impairment on intestinal healing - a potential role for ARHGAP18/RhoA - Marileen M. C. Prins; Francesca P. Giugliano; Manon van Roest; Stan F. J. van de Graaf; Pim J. Koelink; Manon E. Wildenberg (The Company of Biologists, 2021)
The ATG16L1 T300A single-nucleotide polymorphism (SNP) is associated with Crohn's disease and causes an autophagy impairment. We have previously shown that this SNP is involved in the migration and hyperactivation of Rac1 in dendritic cells. Mucosal healing, currently the main target for inflammatory bowel disease treatment, depends on restoration of the epithelial barrier and requires appropriate migration of epithelial cells towards and over mucosal lesions. Therefore, we here further investigated the impact of autophagy on epithelial migration. ATG16L1 knockdown was established in the HT29 human colonic epithelial cell line using lentiviral transduction. Migratory capacity was evaluated using scratch assays and RhoAGTP was measured using G-LISA. Immunofluorescent ARHGAP18 and sequestome 1 (SQSTM1; also known as p62) staining was performed on HT29 cells and primary colonic tissue of Crohn's disease patients. We observed that ATG16L1 knockdown cells exhibited decreased autophagy and decreased migration capacity. Furthermore, activity of RhoA was decreased. These characteristics were phenocopied using ATG5 knockdown and pharmacological inhibition of autophagy. The migration defect was dependent on accumulation of SQSTM1 and was alleviated upon SQSTM1 knockdown. Strikingly, thiopurines also mitigated the effects of impaired autophagy. RhoA dysregulation appeared mediated through accumulation of the upstream regulator ARHGAP18, which was observed in cell lines, human foetal organoids and primary colonic tissue. Our results indicate that the ATG16L1 T300A Crohn's disease-associated SNP causes a decrease in migration capacity in epithelial cells, mediated by an increase in SQSTM1 and ARHGAP18 protein and subsequent reduced RhoA activation.